Single‐center experience of the FIRM technique to ablate paroxysmal and persistent atrial fibrillation. (8th January 2019) - Henley, Patrick; Foreman, Jason R.; Padanilam, Benzy J.; Nair, Girish V.; Olson, Jeff A.; Joshi, Sandeep; Aziz, Zaid; Foster, Todd; Prystowsky, Eric N.
Abstract: Introduction: Focal impulse and rotor modulation (FIRM)‐guided ablation has had mixed results of published success, and most studies have had a follow‐up for a year or less. We aimed to study a consecutive group of patients followed for at least 1.5 years, subgrouped into those with an initial FIRM ablation and those with a previous, failed ablation who now received a FIRM guided one, to evaluate for success in each group and factors that might affect success. Methods: Of 181 patients, 167 were available for analysis. Group 1 (n = 122) had a first or primary ablation (paroxysmal atrial fibrillation [PAF] 51; persistent atrial fibrillation [PeAF] 71) and group 2 (n = 45) had a redo ablation (PAF 18; PeAF 27). All patients were done under general anesthesia. FIRM mapping was done in the right atrium first and then the left, and only rotors consistently seen on multiple epochs were ablated, using 15 to 30 W. Rotor ablation was discontinued when remapping showed elimination of rotational activity at the site. Wide area catheter ablation was done for pulmonary vein isolation (PVI). Routine follow‐up was at 3, 6, and 12 months of the first year, with a Holter monitor at 6 months, and then every 6 months thereafter. Event recorders were given to patients with potential arrhythmic symptoms. Results: Mean follow‐up was 16 months. Nearly 40% of patients had obstructive sleep apnea; mean body mass index was 32; and average left atrial size was 39.7 mm and 46.2 mm for PAF and PeAF patients, respectively. Freedom from atrial arrhythmia recurrence was: in group 1 patients, 82.4% for PAF and 67.6% for PeAF patients; in group 2 patients, 83.3% for PAF, but only 40.7% for PeAF patients. Comparing outcomes for the first 10 patients studied to the next 20 or more done by three operators showed no difference, suggesting no learning curve affecting the ablation results. Furthermore, the univariate analysis did not show any demographic factor to have an independent significance for ablation success or failure. Spontaneous termination during rotor ablation occurred in 76.8% of PAF and 27.6% of PeAF patients but did not affect the long‐term outcomes for maintenance of sinus rhythm. Conclusions: FIRM‐guided atrial ablation plus PVI in our patient population resulted in good success from a recurrence of atrial arrhythmias in patients undergoing an initial ablation procedure. For those with persistent AF undergoing a second procedure now using FIRM guidance plus PVI, the results are lower. Further research is needed to define better the appropriate population for FIRM‐guided ablation and the degree of ablation needed for success in these patients.